Virus sensing receptors in cellular infectivity of influenza A virus - Shaihana Almatrrouk; Iram Saba; Suhair Abozaid; Ahmed A Al-Qahtani; Mohammed N Al-Ahdal (Journal of Infection in Developing Countries)
An innate immune response is essential to mobilize protective immunity upon the infection of respiratory epithelial cells with influenza A virus (IAV). The response is classified as early (nonspecific effectors), local systematic (effector cells recruitment) and late (antigen to lymphoid organ transport, naive B and T cells recognition, effector cells clonal expansion and differentiation). Virus particles are detected by the host cells as non-self by various sensors that are present on the cell surface, endosomes and cytosol. These sensors are collectively termed as pattern recognition receptors (PRRs). The PRRs distinguish unique molecular signatures known as pathogen-associated molecular pattern, which are present either on the cell surface or within intracellular compartments. PRRs have been classified into five major groups: C-Type Lectin Receptor (CLR), Toll-like receptor (TLR), Nod-like receptor (NLR), Retinoic acid-inducible gene-I-like receptor (RLR), which play a role in innate immunity to IAV infection, and the pyrin and hematopoietic interferon-inducible nuclear (PYHIN) domain protein. Here, we discuss the role of PRRs in cellular infectivity of IAV and highlight the recent progress.